Keanekaragaman Serangga Penyerbuk di Pertanaman Jagung Pulut - Sri Nur Aminah; Tamrin Abdullah; Fatahuddin Fatahuddin (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Aminah SN, Abdullah T, Fatahuddin F. 2020. The diversity of Pollinator Insects in Waxy Maize Field. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xxx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Pulut (waxy maize field) is the one of the important commodities in Maros Regency, South Sulawesi. The pollinating insects from Lepidoptera and Hymenoptera found in waxy maize field. The purpose of the research is to identify types of pollinator insects and flowering plant as a food source around the waxy maize field. The research was held in farmer field in Ta'deang village, Maros Regency, South Sulawesi from January to March 2020. The activity in form of field trial in the farmer waxy maize field. Selection source of seeds and agricultural techniques follow farmer habits. The visual observation presence of pollinating insects in the waxy maize was held when the plants 28 DAP (days after planting) through before harvest. The research held visual identification of plant species as producer of nectar and pollen. The result was showed there are six kinds of plant used as a source of food for pollinator insects living in the habitat of waxy maize field. Flowering plants categorized as weeds are: Portulaca sp., Lantana camara and Cleome rutidosperma are source of nectar and pollen. The Shannon-Wiener diversity index for pollinator insects is -1.5 indicates that the diversity is very low, population development is under environmental stress and the ecosystem is unstable. The highest total of insect population as butterfly Catopsilia scylla family Pieridae and the lowest was Graphium agamemnon, family Papilionidae. The conclusion is: the dominant pollinator insects in waxy maize from Lepidoptera is Catopsilia scylla and the dominant Hymenoptera order is Apis mellifera (honey bee).